Pluralitas Masyarakat dalam Islam - Joko Widodo (Kopertais Wilayah X Jawa Tengah, 2017)
AbstractPlurality is a fact and can not be denied in society, Islam as a moderate religion, which a justice, and always invites people to facilitate religious and possess compassion for fellow human beings. Islam rejects the conservative attitudes, opacity, and setbacks. On the other hand, Islam also rejects definitively all forms of oppression, hostility, murder, and destruction (on behalf of unifying the Ummah). All humans in the natural world was created from the same origin. No excess of one than the other, but the most good in the discharge of its functions sebagimana caliph of God on earth, which is more useful for humanity, and the most piety to Allah SWT. Differences of race and nation merely as a sign and identity in social life of society. Islam recognizes the plurality, as in Q.S. Al-Hujurat verse; 13. Islam recognizes the differences in nation, tribe, ethnicity and language. This diversity can not be deleted. But Islam is able to cope with this diversity or differences.Kata Kunci: Pluralitas Masyarkat, Islam